2020
DOI: 10.18311/jnr/2020/24240
|View full text |Cite
|
Sign up to set email alerts
|

Anti-elastase, Antioxidant, Total phenolic and Total Flavonoid Content of Macassar Kernels (Rhus javanica L) from Pananjung Pangandaran Nature Tourism Park- Indonesia

Abstract: Background: Phytochemicals are present as important substances in natural resources and therefore, have aided in invention of the anti-oxidant, and anti-elastase properties of polyphenol compounds present in Indonesian herbs such as Macassar Kernels (Rhus javanica L). Objective: This research aimed to investigate anti-elastase, and antioxidant properties. Methods: Ethanolic extract of Rhus Leaves (RL), Rhus Stem (RS), Rhus Greenish Fruit (RGF), and Rhus Blackish-grey Fruit (RBF) were prepared individually by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(21 reference statements)
1
7
0
2
Order By: Relevance
“…It was observed that DPPH free radical-scavenging activity of the extract (1.2, 4.63, and 22.86 mg AAE/g n-hexane, acetone, and 80% aqueous methanol respectively) due to the presence of a relatively higher value of total phenol and total flavonoid contents as shown in Previous studies showed the plants of the genus Rhus used in this study, namely Rhus typhina and Rhus javanica reported. The result of Rhus typhina is much better than DPPH radicalscavenging activities reported by on the ethanol fruit extract (3.99, 6.67, and 81.86% at 12.5, 25, and 50 mg/ml, respectively) [4] and the ethanolic extracts of Rhus javanica using DPPH the IC50 values leaves (157.699), steam (561.046), greenish fruit (189.31), and blackish-grey fruit (239.276) using Gallic acid standards [18]. Our results confirm those of Odongo et al(2017) reporting substantial antioxidant activity plant parts from this species.…”
Section: Total Antioxidant Activitymentioning
confidence: 88%
See 1 more Smart Citation
“…It was observed that DPPH free radical-scavenging activity of the extract (1.2, 4.63, and 22.86 mg AAE/g n-hexane, acetone, and 80% aqueous methanol respectively) due to the presence of a relatively higher value of total phenol and total flavonoid contents as shown in Previous studies showed the plants of the genus Rhus used in this study, namely Rhus typhina and Rhus javanica reported. The result of Rhus typhina is much better than DPPH radicalscavenging activities reported by on the ethanol fruit extract (3.99, 6.67, and 81.86% at 12.5, 25, and 50 mg/ml, respectively) [4] and the ethanolic extracts of Rhus javanica using DPPH the IC50 values leaves (157.699), steam (561.046), greenish fruit (189.31), and blackish-grey fruit (239.276) using Gallic acid standards [18]. Our results confirm those of Odongo et al(2017) reporting substantial antioxidant activity plant parts from this species.…”
Section: Total Antioxidant Activitymentioning
confidence: 88%
“…The methanolic extract of leaves, stem, and fruit of the Rhus pentaphylla were 71.16, 141.79, 76.88, and Rhus tripartite 64.13, 108.83, and 75.16 respectively in (mg GAE g −1 DW) [17]. On the contrary, the ethanolic extracts of Rhus javanica from leaves (51.91±0.01), steam (28.5 ± 0.03), greenish fruit (53.66 ± 0.01), and blackish-grey fruit (32.74 ± 0.03) using Gallic acid standards [18] is less than the value obtained in this study. This difference could be the difference in the species, environmental (e.g., season, temperature, light, soil), and genetic factors that determine the variation of the antioxidant activity of these compounds.…”
Section: Concentration Vs Absorbancementioning
confidence: 99%
“…[7]. In the previous research, stem extract of Rhus javanica had the best percent inhibition of elastase activity compared to extract from leaves and fruits (greenish and blackish-grey) [8].…”
Section: Introductionmentioning
confidence: 89%
“…The methanolic extracts of leaves, stem, and fruit of the Rhus pentaphylla were 71.16, 141.79, 76.88, and Rhus tripartite 64.13, 108.83, and 75.16, respectively in (mg GAE g − 1 DW) [32]. Another report also revealed an evaluation of total phenolic contents in ethanolic extracts of Rhus javanica from leaves (51.91 0.01), steam (28.5 ± 0.03), greenish fruit (53.66 ± 0.01), and blackish-grey fruit (32.74 ± 0.03) using Gallic acid standards [33] all reports were less than the value obtained in this study. This difference could be the difference in the species, environmental (e.g., season, temperature, light, soil), and genetic factors that determine the variation of the antioxidant activity of these compounds.…”
Section: Total Phenol Total Avonoid Contentsmentioning
confidence: 94%